Adjusting to New Normal: Peer Coaching as Professional Development Strategies for Early Childhood and Primary Education Teacher - Esya Anesty Mashudi; Nenden Sundari; Ima Ni’mah Chudari (Program Studi PGSD Kampus UPI di Serang, 2020)
Along with the spread of COVID-19 where physical contact is limited, social interactions have shifted from offline to online, all forms of activity have become digitalized. The development of professionalism of educators is one of the fields that should not be hampered by physical or social restrictions. The educational process continues and requires educators to become more competent in their fields. So far, many studies, research, and literature discuss various things about what needs to be done to support the student learning process, however, publications that discuss teacher professional development are still minimal. A search of various teacher training models leads to a discussion of the peer coaching method, which is a professional development model that can be used to develop the teaching process. Peer coaching requires teachers to reflect on their teaching practices, share what works and useful suggestions, as well as learn from or with colleagues, both seniors and beginners, to establish collaborative and professional relationships to discuss various problems and challenges related to teaching. in the new normal era. This study exposed the result of conducting peer coaching models for professional development of teachers in new normal era and it’s further applicability based on benefits obtained by the teachers. Data was analyzed using qualitative inquiry, described descriptively and discussed based on the theory and experiences of both coach and coachee. According to the results of this study, peer coaching was found to be an prospective tool for professional development of teachers in K-6 Grade particularly in the new normal era, because it offers teachers with the opportunity to be involved in a small group of people, obtaining new skills for teaching practices, assures self-reflection, sharing experience, and mutual growth among members